Hypertrophy Stimulation at the Onset of Type I Diabetes Maintains the Soleus but Not the EDL Muscle Mass in Wistar Rats - Fortes, Marco A. S.; Scervino, Maria V. M.; Marzuca-Nassr, Gabriel N.; Vitzel, Kaio F.; da Justa Pinheiro, Carlos H.; Curi, Rui (Frontiers in Physiology, 2017)
Diabetes mellitus induces a reduction in skeletal muscle mass and strength. Strength training is prescribed as part of treatment since it improves glycemic control and promotes increase of skeletal muscle mass. The mechanisms involved in overload-induced muscle hypertrophy elicited at the establishment of the type I diabetic state was investigated in Wistar rats. The purpose was to examine whether the overload-induced hypertrophy can counteract the hypotrophy associated to the diabetic state. The experiments were performed in oxidative (soleus) or glycolytic (EDL) muscles. PI3K/Akt/mTOR protein synthesis pathway was evaluated seven days after overload-induced hypertrophy of soleus and of EDL muscles. The mRNA expression of genes associated with different signaling pathways that control muscle hypertrophy was also evaluated: mechanotransduction (FAK), Wnt/β-catenin, myostatin and follistatin. The soleus and EDL muscles when submitted to overload had similar hypertrophic responses in control and diabetic animals. The increase of absolute and specific twitch and tetanic forces had the same magnitude as muscle hypertrophic response. Hypertrophy of the EDL muscle from diabetic animals mostly involved mechanical loading-stimulated PI3K/Akt/mTOR pathway besides the reduced activation of AMP-activated protein kinase (AMPK) and decrease of myostatin expression. Hypertrophy was more pronounced in the soleus muscle of diabetic animals due to a more potent activation of rpS6 and increased mRNA expression of insulin-like growth factor-1 (IGF-1), mechano-growth factor (MGF) and follistatin, and decrease of myostatin, MuRF-1 and atrogin-1 contents. The signaling changes enabled the soleus muscle mass and force of the diabetic rats to reach the values of the control group.